Multi-Component Adsorption Studies on LiLSX and CMS for Helium Separation - Nisith Kr. Das; Pradeep Kumar; C. Mallik; Rakesh K. Bhandari (Adsorption Science & Technology)
An experimental study is reported on the purification of helium gas from a ternary mixture of helium (30 mol%), nitrogen (60 mol%) and oxygen (10 mol%) employing a single-column Pressure Swing Adsorption (PSA) process. Appropriate adsorbents were selected for effecting this separation by exploiting adsorption equilibrium isotherm and breakthrough measurements in order to choose the optimum operating conditions for the PSA process. The adsorption and breakthrough characteristics for the pure gas as well as for the mixed gases were also examined. The pure gas adsorption isotherms were obtained employing a static method, while mixed gas adsorption studies were undertaken using a volumetric chromatography technique. Computer simulations, along with breakthrough experiments, were performed to study the adsorption dynamics and thereby identify suitable operating parameters as well as vessel dimensions. Based on these data, a single-column PSA system has been developed for the separation of helium gas. The selection of adsorbent, effect of feed pressure, flow rate and cycle time related to the process performance has been established. It was noted that employing an adsorbent such as LiLSX at a flow rate of 2 ℓ/min, a working pressure of 500 kPa and a feed time of 180 s appears to be appropriate for obtaining 98.3% pure He with 65% recovery for the column dimensions chosen.